Peningkatan Literasi Artificial Intelligence untuk Mendukung Belajar dan Produktivitas melalui Webinar Nasional Kolaborasi Perguruan Tinggi - Herlawati; Rahmadya Trias Handayanto; Rakhmat Purnomo; Anindita Septiarini (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed education and professional practices. However, maximizing the benefits of AI requires adequate digital literacy to ensure its effective, ethical, and responsible use. This community engagement program aimed to improve Artificial Intelligence literacy for learning and productivity through a National Collaborative Webinar involving multiple higher education institutions. The webinar was conducted online via Zoom Meeting on May 23, 2026, involving 345 participants from universities, schools, and other institutions across eight provinces in Indonesia. The implementation consisted of planning, material development, webinar promotion, pre-test, interactive presentations, and hands-on practice using AI applications such as ChatGPT, Claude, and Mendeley AI, followed by a post-test and participant satisfaction evaluation. The results demonstrated that the webinar successfully reached participants from diverse professional and institutional backgrounds. The comparison between pre-test and post-test results indicated improvements in most evaluation indicators, particularly participants’ intention to continuously use AI in learning and daily work, which increased from 35.7% to 41.9%. Participants’ ability to critically evaluate AI-generated outputs also increased from 43.2% to 44.8%, while the perception that AI improves task efficiency increased from 46.4% to 47.0%. These findings indicate that a collaborative national webinar is an effective community engagement approach to enhancing AI literacy while encouraging the productive and responsible adoption of AI technologies in education and professional activities.